Two Lysine Sites That Can Be Malonylated Are Important for LuxS Regulatory Roles in Bacillus velezensis - Xianming Cao; Yulong Li; Jialu Fan; Yinjuan Zhao; Rainer Borriss; Ben Fan (Microorganisms, 2021)
S-ribosylhomocysteine lyase (LuxS) has been shown to regulate bacterial multicellular behaviors, typically biofilm formation. However, the mechanisms for the regulation are still mysterious. We previously identified a malonylation modification on K124 and K130 of the LuxS in the plant growth-promoting rhizobacterium B. velezensis (FZB42). In this work, we investigated the effects of the two malonylation sites on biofilm formation and other biological characteristics of FZB42. The results showed that the K124R mutation could severely impair biofilm formation, swarming, and sporulation but promote AI-2 production, suggesting inhibitory effects of high-level AI-2 on the features. All mutations (K124R, K124E, K130R, and K130E) suppressed FZB42 sporulation but increased its antibiotic production. The double mutations generally had a synergistic effect or at least equal to the effects of the single mutations. The mutation of K130 but not of K124 decreased the in vitro enzymatic activity of LuxS, corresponding to the conservation of K130 among various Bacillus LuxS proteins. From the results, we deduce that an alternative regulatory circuit may exist to compensate for the roles of LuxS upon its disruption. This study broadens the understanding of the biological function of LuxS in bacilli and underlines the importance of the two post-translational modification sites.